Development Of A Control Model For A Head On Collision Avoidance System - Ismail, Mohamad Azren (Universiti Sains Malaysia, 2021)
The autonomous cars relate to sensor technologies to offer real time information about the environment of the traffic situation. The information that been collected will increase the driving efficiency and respond so that it will offer comfort in the meantime boosts the safety of the driver. This thesis investigates and simulates the creation of a head-on collision control model for a vehicle overtaking a front truck while at the opposite lane a vehicle travelling in the opposite direction. This will show how an autonomous vehicle's algorithm determines whether to pass the front cars or not based on the distances and speeds of the opposing vehicles. The time it takes to overtake the front vehicles is roughly 12 seconds, with a 2 second safety margin. According to the simulation, the system would opt to continue the passing procedure if the time needed for the opposing cars to reach the passing vehicles' distances is greater than 12 seconds, and vice versa if the vehicles decide not to pass the front vehicles.